2014
DOI: 10.1038/ncomms4016
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency cell-specific targeting of cytokine activity

Abstract: Systemic toxicity currently prevents exploiting the huge potential of many cytokines for medical applications. Here we present a novel strategy to engineer immunocytokines with very high targeting efficacies. The method lies in the use of mutants of toxic cytokines that markedly reduce their receptor-binding affinities, and that are thus rendered essentially inactive. Upon fusion to nanobodies specifically binding to marker proteins, activity of these cytokines is selectively restored for cell populations expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 42 publications
3
75
0
Order By: Relevance
“…Antigen choice also impacts targeting efficacy: in contrast to our results, several studies have shown that immunocytokines specific for antigens expressed by tumor vasculature or liquid/disseminated tumors perform better than irrelevant immunocytokines (4,7,34), likely because these antigens are in closer contact with the blood and thus, more accessible than solid tumor antigens. Alternatively, the affinity of the cytokine for its receptor can be weakened, so that cytokine function is potentially restored only on high-avidity binding to tumor cells (35). Finally, our mathematical model suggests that small-format immunocytokines may intrinsically exhibit better antigen-targeting specificity than large-format immunocytokines because of size-dependent transport properties (rapid systemic clearance and diffusion by smaller molecules).…”
Section: Discussionmentioning
confidence: 97%
“…Antigen choice also impacts targeting efficacy: in contrast to our results, several studies have shown that immunocytokines specific for antigens expressed by tumor vasculature or liquid/disseminated tumors perform better than irrelevant immunocytokines (4,7,34), likely because these antigens are in closer contact with the blood and thus, more accessible than solid tumor antigens. Alternatively, the affinity of the cytokine for its receptor can be weakened, so that cytokine function is potentially restored only on high-avidity binding to tumor cells (35). Finally, our mathematical model suggests that small-format immunocytokines may intrinsically exhibit better antigen-targeting specificity than large-format immunocytokines because of size-dependent transport properties (rapid systemic clearance and diffusion by smaller molecules).…”
Section: Discussionmentioning
confidence: 97%
“…The mutation Q124R was introduced into the IFNa2 sequence by site-directed mutagenesis using the QuikChange II-E Site-Directed Mutagenesis Kit (Agilent Technologies) and sdAb were generated at the VIB Protein Service Facility, as described previously (17). AFNs (hIFNa2Q124R or hIFNaR149A coupled via a 20xGGS-linker to an N-terminal targeting sdAb) were constructed in pHen6 vectors, large-scale productions of His-tagged AFNs were performed in E. coli.…”
Section: Construction and Production Of Afns And Immunocytokinesmentioning
confidence: 99%
“…16). To improve the therapeutic index of toxic cytokines, we recently protein-engineered AcTakines (Activated-by-Targeting cytokines), optimized immunocytokines that use mutated cytokines with strongly reduced affinity for their receptor complex instead of WT cytokines (17). Fusing the mutated cytokine to cell-specific targeting domains specifically targets them to the selected cell population, restoring the AcTakine activity at that particular cell population with an up to 3-log targeting efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…For example, AcCS might be used to increase the activity of natural IFNs produced locally at the site of a viral infection. In addition, several recent studies have demonstrated targeting IFNs to specific cells can be accomplished using IFN fusion proteins, which target IFNs to various cell surface markers by a variety of binding proteins (9,20,45). Improved targeting efficiency of IFN fusion proteins was recently demonstrated by reducing IFN-IFNAR2 binding affinity (9).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several recent studies have demonstrated targeting IFNs to specific cells can be accomplished using IFN fusion proteins, which target IFNs to various cell surface markers by a variety of binding proteins (9,20,45). Improved targeting efficiency of IFN fusion proteins was recently demonstrated by reducing IFN-IFNAR2 binding affinity (9). Combining IFN fusion proteins with AcCS may allow the targeted IFNs to be further inactivated to further improve targeting specificity but allow them to be re-activated using AcCS.…”
Section: Discussionmentioning
confidence: 99%